Incidence of ischemic complications and technical nuances of arteries preservation for insular gliomas resection - Hou, Zonggang; Huang, Zhenxing; Li, Zhenye; Deng, Zhenghai; Li, Gen; Xu, Yaokai; Wang, Mingran; Sun, Shengjun; Zhang, Yazhuo; Qiao, Hui; Xie, Jian (Frontiers in Surgery, 2022)
Introduction Insular gliomas have a complex anatomy and microvascular supply that make resection difficult. Furthermore, resection of insular glioma is associated with a significant risk of postoperative ischemic complications. Thus, this study aimed to assess the incidence of ischemic complications associated with insular glioma resection, determine its risk factors, and describe a single surgeon’s experience of artery-preserving tumor resection. Methods We enrolled 75 consecutive patients with insular gliomas who underwent transcortical tumor resection. Pre- and postoperative demographic, clinical, radiological (including diffusion-weighted imaging [DWI]), and intraoperative neurophysiological data, and functional outcomes were analyzed. Motor evoked potentials (MEPs) and radiological characteristics like: relationship between the proximal segment of the LLSAs and the tumor, the flat inner edge sign (the inner edge of the insular glioma is well-defined) or obscure inner edge sign, the distance between the lesion and posterior limb of the internal capsule and the invasion of the superior limiting sulcus by the tumor were analyzed. Strategies such as “residual triangle”, “basal ganglia outline reappearance” and “sculpting” technique were used to preserve the lateral lenticulostriate arteries (LLSAs) and the main branches of M2 for maximal tumor resection according to the Berger-Sinai classification. Results Postoperative DWI showed acute ischemia in 44 patients (58.7%). Moreover, nine patients (12%) had developed new motor deficits, as determined by the treating neurosurgeons. The flat inner edge sign (odds ratio [OR], 0.144; 95% confidence interval [CI], 0.024–0.876) and MEPs (>50%) (OR, 18.182; 95% CI, 3.311–100.00) were significantly associated with postoperative core ischemia, which affected the posterior limb of the internal capsule or corona radiata. Conclusions Insular glioma resection was associated with a high incidence of ischemia, as detected by DWI, as well as new motor deficits that were determined by the treating neurosurgeons. Patients with tumors, who had obscure inner edge sign and intraoperative MEPs decline > 50%, had a higher risk of developing core ischemia. With our strategies, maximal safe resection of insular gliomas may be achieved.